2019
DOI: 10.1021/acs.langmuir.8b04203
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Photoactivation of Self-Assembled Monolayers to Direct Cell Adhesion and Migration

Abstract: Dynamic substrates for cell culture control the spatial and temporal presentation of extracellular matrix ligands that interact with adherent cells. This paper reports a photoactive surface chemistry that can repeatedly activate regions of the substrate for cell adhesion, spreading, and migration. The approach uses self-assembled monolayers presenting the integrin ligand RGD that is caged with a nitrophenyl-based photoprotecting group. The group is also modified with a maltoheptaose oligosaccharide to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…117 Current research in this applicational area is focused on the fabrication of dynamic surfaces, through supramolecular approaches 114 or activation with external stimuli (e.g. light, electrical potentials) that are cell-compatible and allow multiple cycles of activation, 110 as well as on the increasing sophistication of the SAMs platforms (e.g., automation, robotisation), interfaced with mass spectrometry analytics, 233 to support and advance high throughput screening (HTS) programs 112 in drug discovery and diagnostics. The findings from these early studies revealed new potential applications, notably biosensing.…”
Section: Final Overview Challenges and Prospectsmentioning
confidence: 99%
“…117 Current research in this applicational area is focused on the fabrication of dynamic surfaces, through supramolecular approaches 114 or activation with external stimuli (e.g. light, electrical potentials) that are cell-compatible and allow multiple cycles of activation, 110 as well as on the increasing sophistication of the SAMs platforms (e.g., automation, robotisation), interfaced with mass spectrometry analytics, 233 to support and advance high throughput screening (HTS) programs 112 in drug discovery and diagnostics. The findings from these early studies revealed new potential applications, notably biosensing.…”
Section: Final Overview Challenges and Prospectsmentioning
confidence: 99%
“…A self-assembled monolayer (SAM), a material of high quality, can be selected for constructing ideal bionic models. Over the past decades, the SAM has obtained much attention by researchers in various fields. In the field of electronics, the SAM has been designed as molecular rectifier, and the large magnitude of rectification can be utilized in device platforms. Subsequently, scientists have inspected the effects of molecular length, structure defects, and the heterogeneity on the electronic performance. Further research shows that the charge transfer across a SAM can be regulated by molecular polarizability, ionic pair, hydrogen bond, donor–acceptor system, and functional groups. These surface engineering investigations have made great contributions to molecular electronics. In the field of bionics, Anderson et al have examined the 11-mercaptoundecanoic acid (MUA) SAM, and claimed that the electrochemical behavior on this SAM can be regulated by substrate potential and pH .…”
Section: Introductionmentioning
confidence: 99%